2021
DOI: 10.3390/d13040160
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Campomanesia adamantium and Its Correlation with Land Use and Land Cover

Abstract: (1) Background: Campomanesia adamantium is an endemic species of the Cerrado and this biome has been under threat by its constant degradation. The genetic diversity of C. adamantium was characterized using species-specific microsatellites in two different time periods and correlations of these parameters of genetic diversity with the land use and land cover data. (2) Methods: We used 10 microsatellite loci to analyze C. adamantium from five populations, collected in 2011 and 2017. Maps of land use and land cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Areas with more secondary vegetation presented higher genetic diversity, which represents high adaptive potential of species concerning environmental changes, and a high inbreeding coefficient was observed with exposed soil nearby, which may indicate that pollination among individuals could have been affected by distance, intensification of agriculture and pesticide exposure. They concluded that a decreased gene flow in C. adamantium population and an increased inbreeding rate indicates environmental degradation influenced by land use and land cover (Crispim et al, 2021). Despite those finds, C. adamantium has an incredible recovery capacity after several days of drought and could, therefore, be used to restore degraded areas (Junglos et al, 2016).…”
Section: The Agroforestry Model Enabling the Ecosystem Restorationmentioning
confidence: 99%
“…Areas with more secondary vegetation presented higher genetic diversity, which represents high adaptive potential of species concerning environmental changes, and a high inbreeding coefficient was observed with exposed soil nearby, which may indicate that pollination among individuals could have been affected by distance, intensification of agriculture and pesticide exposure. They concluded that a decreased gene flow in C. adamantium population and an increased inbreeding rate indicates environmental degradation influenced by land use and land cover (Crispim et al, 2021). Despite those finds, C. adamantium has an incredible recovery capacity after several days of drought and could, therefore, be used to restore degraded areas (Junglos et al, 2016).…”
Section: The Agroforestry Model Enabling the Ecosystem Restorationmentioning
confidence: 99%
“…Genetic variation in plant species is strongly affected by several historical and demographic factors, including geographic distribution, life form, and population size [56]. The results of AMOVA showed that most of the genetic diversity was found within C. prunifera populations (Table 3).…”
Section: Plos Onementioning
confidence: 99%